Shoot proliferation from potato (Solanum tuberosum cv. Agria) under different concentration of MS include vitamins and BAP medium - Kazemiani, Samaneh; Motallebi-Azar, Ali Reza; Panahandeh, Jaber; Mokhtarzadeh, Sam; Ozdemir, Fethi Ahmet (Progress in Nutrition, 2018)
The present investigation was conducted to develop a protocol for rapid shoot proliferation of potato by MS medium and different concentrations of plant growth regulators. In this study, the node explant was cultured in MS media supplemented with different concentrations of thiamine-HCl (0.1 and 10 mg.l-1), Pyridoxine- HCl, Nicotinic acid (each 0.5 and 50 mg.l-1) and BAP (0.0, 2 and 4 mg.l-1) for shoot proliferation. Maximum number of lateral shoots was observed in MS medium containing 50 mg.l-1 Nicotinic acid, 50 mg.l-1Pyridoxine- HCl, 10 mg.l-1Thiamine-HCl and 4 mg.l-1BAP. Also, maximum percentage of root and callus formation was observed in combination of MS include vitamins without BAP, the present study describes an efficient method for in vitro shoot proliferation of potato cultivars which could be considered for large scale multiplication and propagation of this important vegetable crop.